Genes and Pseudogenes: Complexity of the RCCX Locus and Disease - Carrozza, Cinzia; Foca, Laura; De Paolis, Elisa; Concolino, Paola (Frontiers in Endocrinology, 2021)
Copy Number Variations (CNVs) account for a large proportion of human genome, are responsible for a wide spectrum of diseases and disease susceptibilities and are a primary contributor to human phenotypic variation. Multiallelic CNVs represent a considerable fraction of large CNVs and are closely associated with segmental duplications by virtue of their prevalent duplicate alleles. RCCX CNV is a complex, multiallelic and tandem CNV located in the major histocompatibility complex (MHC) class III region. RCCX structure is traditionally described by the copy number of a DNA segment where four genes- serine/threonine kinase 19 (STK19), complement 4 (C4), steroid 21-hydroxylase (CYP21), and tenascin-X (TNX)- reside close to each other. In the Caucasian population, the most common RCCX haplotype (69%) consists of two segments wherein the orientation of genes, from telomere to centromere, is STK19-C4A-CYP21A1P-TNXA-STK19B-C4B-CYP21A2-TNXB. Nonallelic homologous recombination (NAHR) contributes substantially to the genetic diversity of RCCX: unequal crossover facilitates large structural rearrangements and copy number changes, whereas gene conversion mediates relatively short sequence transfers. The results of these events increased the RCCX genetic diversity and are responsible of specific human diseases. This review provides an overview on RCCX complexity pointing out the molecular bases of Congenital Adrenal Hyperplasia (CAH) due to CYP21A2 deficiency, CAH-X Syndrome and disorders related to CNV of complement component C4.